2020
DOI: 10.5267/j.msl.2020.3.025
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of human resource management practices on employees’ motivation and loyalty

Abstract: The research was conducted in order to identify the relationships between human resource practices, employee motivation and employee loyalty. Quantitative research method was applied with questionnaires directly delivered to 595 employees in hospitality sector in Ho Chi Minh city, Vietnam. Statistics techniques including exploratory factor analysis, reliability analysis, multiple regression and mediation analysis were used. The empirical results showed that variables of team spirit, career development, compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
0
9
0
3
Order By: Relevance
“…With this study, we also understand the important role of loyalty, as managers could create a positive organizational climate and some human resources practices that could boost employees' MRJIAM 22,1 loyalty. For instance, Khuong et al (2020) performed a study to evaluate the relationship between human resources practices and employees' loyalty through employees' motivation. The results suggested that increasing team spirit, career development, compensation, relationship with manager and working environment may lead to high levels of loyalty.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…With this study, we also understand the important role of loyalty, as managers could create a positive organizational climate and some human resources practices that could boost employees' MRJIAM 22,1 loyalty. For instance, Khuong et al (2020) performed a study to evaluate the relationship between human resources practices and employees' loyalty through employees' motivation. The results suggested that increasing team spirit, career development, compensation, relationship with manager and working environment may lead to high levels of loyalty.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…Pētnieki ir uzskaitījuši vairākus dažādus faktorus, kas ietekmē darbinieku lojalitāti: algu, pabalstus, paaugstināšanu amatā, stimulus un daudzus citus. Būtībā šie faktori rada darbinieku motivāciju, kas veicina lojalitātes attīstību (Khuong et al, 2020).…”
Section: Lojalitātes Jēdziens Un Būtībaunclassified
“…Subsequently, an increasing number of studies have endeavored to investigate the impact of employee loyalty on organizations. These studies indicate that loyal employees exhibit higher attachment (Turkyilmaz et al , 2011), greater satisfaction (Khuong et al , 2020) and reduced turnover intention (Oh et al , 2023). Notably, existing studies predominantly concentrate on examining the human capital-related outcomes of employee loyalty, leaving other nonhuman capital-related outcomes largely unexplored.…”
Section: Introductionmentioning
confidence: 98%